Exercise Prescription in Cardiac Rehabilitation A Practical Approach to Early Mobilization and Exercise Training - Staron, Adam; Wolszakiewicz, Jadwiga; AlSulaimi, Meteb (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The use of ingredients obtained from waste is becoming a necessity to reduce worldwide pollution, saving both environment and earth biodiversity. In fact, according to Fritjof Capra "The survival of humanity will depend from our ecological knowledge, the capacity of understanding the fundamentals of ecology and to live accordingly with them". Please see the complete preface attached.